In Vitro Antimicrobial Activity of Brachythecium campestre and Eurhynchium pulchellum Extracts - Tonguc Yayintas, O.; Mericli Yapici, B. (Asian Journal of Chemistry, 2010)
The purpose of this research was to examine the in vitro antimicrobial activity of ethanol extracts of Brachythecium campestre (E1) and Eurhynchium pulchellum (E2). The antimicrobial activity of the E1 and E2 was evaluated according to the disc diffusion method against 10 test bacteria, including 4 Gram-positive (Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 122228, Streptococcus faecalis NRRLB-14617, Bacillus cereus ATCC 11778), 6 Gram-negative bacteria (Salmonella typhi CCM 5445, Proteus vulgaris ATTC 68, Enterobacter aerogenes ATCC 13043, Pseudomonas aureginosa ATTC 27853, Escherichia coli ATCC 25922, Neisseria canis) and 9 test yeasts (Saccharomyces cerevisiae ATCC 9763, Saccharomyces colombia, Saccharomyces uvarum, Schizosaccharomyces pombe, Kluyveromyces marxianus, Debarymyces hansenii, Candida lypolitica, Geotricum candidum and Rhodotorula rubra DSM 70403). Present results showed that the extracts possessed antibacterial and antiyeast effect against the majority of the bacteria and all of the yeasts tested.